Abbreviations in Medieval Medical Manuscripts - De la Cruz-Cabanillas, Isabel; Diego-Rodríguez, Irene (SELIM. Journal of the Spanish Society for Medieval English Language and Literature, 2019)
Understanding the large number of abbreviations present in any medieval manuscript is one of the essential skills required by any knowledgeable palaeographer. English medieval manuscripts contain a great variety of abbreviations which were transferred from Latin and applied to the vernacular. As a result, their reasonably standard Latin system lost consistency. Editorial practice should avoid intervention, as it may detract from the originality and the text distinct and stylistic features. However, it is crucial to expand abbreviations coherently to carry out further analysis from a historical linguistic perspective. Thus, this article aims to demonstrate how the way in which a palaeographer transcribes specific abbreviations has an impact on the establishment of the dialectal provenance of a Middle English manuscript. In order to do so, we shall analyse the abbreviations extracted from a corpus of medical manuscripts and bring to light their relevance as far as English historical dialectology is concerned. Keywords: abbreviations; Middle English; medical manuscripts